How can CBAM work? Options for improving Europe's carbon border adjustment mechanism - Gabriel Felbermayr; Hendrik Mahlkow; Isabel Pham; Robin Sogalla; Joschka Wanner (Stiftung Familienunternehmen, 2025)
The EU aims to reduce its CO₂ emissions by 55% by 2030 compared with 1990 levels, and by 90% by 2040 relative to 1990. To achieve these ambitious climate targets, the volume of available emission allowances will have to be drastically reduced in the coming years. This will lead to a sharp rise in the price of these emission allowances.
Keywords: 330; Location; Climate; Trade; Europe